USING NIGELLA SATIVA OIL SEED MEAL IN FEEDING AWASSI EWES 1 -EFFECT ON SOME PRODUCTION AND REPRODUCTIVE TRAITS - Qussay Z.Shams Al-Dain (Mesopotamia Journal of Agriculture, 2005)
This study was conducted by using 72 awassi ewes at different ages (3,4 and 5 years ).The ewes were divided into three groups and these groups were fed on three rations different in nigella sativa oil seed meal percentage(0,7 and 14%) since 45 days before mating season and until the end of lactation season.the effect of using different percentages of nigella sativa oil seed meal were studied on some production and reproductive traits.The results indicated that using of nigella sativa oil seed meal has significantly effected most studied traits,ewes weight,lambs weight at birth and at weaning, milk production for pre-weaning ,commercial , total milk, length of lactation and the percentages of fertility , prolificacy at lambing and at weaning, lambs livability until weaning , protein and total sold not fat were increased significantly (p<0.05 ),while the percentages of barreness, fat and total solid were decrease significantly (p<0.05 ) by increasing the percentage of nigella sativa oil seed meal in ration , while length of gestation ,percentages of lactose and ash has non significantly effect by feeding nigella sativa oil seed meal. Also the age of ewe has significantly (p<0.05) effect the percentages of fertility, prolificacy at lambing and weaning , barrenness and weights of lambs at birth and at weaning only.